Utilization of Digital Platforms and Social Media in Marketing Products of the PKK Group in Improving the Economy and Food Security of Batu Rejo Villagers - Br Ginting, Dewi Sartika; Harumy, T. Henny Febriana; Huzaifah, Ade Sarah; Rosalia, Vicky; Saragih, Mhd Afifan Aly Rahman; Dalimunthe, Muhammad Daud Arbani Asfi; Arrahmi, Ridha; Jernih (Talenta Publisher, 2023)
After the millennium era, the development of information technology has become quite fast, and changes in business patterns have also increased sharply. One of them is in the world of marketing. During the pandemic and post-pandemic times, digital transformation has been carried out, namely digital marketing or marketing products in cyberspace. Community service is one of the right ways to carry out the socialization of information technology in marketing techniques to support economic development. The community service that will be carried out is entitled Utilization of Digital Platforms and Social Media in Marketing Product Creativity for the PKK Desa Batu Rejo Group, to help the PKK Desa Batu to produce products that will be marketed online through digital platforms and social media that are already widely used by people. PKK groups will be guided and trained to be able to manufacture and market their products in the online market, so they can remain productive even from home. The activities carried out in this service are workshops on digital platforms and social media as well as training on their utilization in online marketing of the creative products of the PKK Batu Rejo Village group.